Makna Teologis Kata Perhentian dalam Ibrani 4:1-14 (Analisis Tekstual, Stuktural, Kontekstual dan Intertekstual) - Daniel Lindung Adiatma; Saul Arlos Gurich (HUPERETES: Jurnal Teologi dan Pendidikan Kristen, 2021)
There is a tendency for many commentators of the New Testament to interpret the text with a topical approach. This approach is relevant for research in the field of Christian theology. The problem is, that the topical approach has a tendency to ignore the unity of the elements of the book. Therefore, we need a model of topical interpretation that is perfected with the unity of the theology of the book. The topic of the theological meaning of the word "rest" has attracted the attention of interpreters recently. These topics are the small sections that make up the theology of the book of Hebrews as a whole. This article presents three analyses (textual, contextual, and intertextual) as an approach to finding the theological meaning of the word "rest" in Hebrews 4:1-14. The author considers the book of Hebrews as the final form to find the meaning of the word "rest" in the theological context of the book of Hebrews. The author tries to synchronize the three approaches in finding the progressive meaning of the word "cessation" in both the Old Testament and the New Testament. The results of research through these three approaches have shown an increase in the meaning of the word "rest" from the context of the Old and New Testaments. Finally, this article can support the theory of progressive revelation that dispensational evangelicals have long believed.Ada kecenderungan penafsir kitab Perjanjian Baru menafsirkan teks dengan pendekatan topikal. Pendekatan ini relevan bagi penelitian pada bidang teologi Kristen. Masalahnya, pendekatan topikal memiliki kecenderungan mengabaikan kesatuan unsur-unsur kitab. Oleh karena itu, diperlukan suatu model penafsiran topikal yang disempurnakan dengan kesatuan teologi kitab. Topik tentang makna teologi kata “perhentian” menarik perhatian para penafsir pada akhir-akhir ini. Topik tersebut merupakan bagian kecil yang membangun teologi kitab Ibrani secara keseluruhan. Artikel ini memaparkan tiga analisa (tekstual, kontekstual dan intertekstual) sebagai pendekatan untuk menemukan makna teologi kata “Perhentian” dalam kitab Ibrani 4:1-14. Penulis mempertimbangkan kitab Ibrani sebagai bentuk akhir untuk menemukan makna kata “perhentian” dalam konteks teologi kitab Ibrani. Penulis berusaha melakukan sinkronisasi tiga pendekatan tersebut dalam menemukan progresifitas makna kata “Perhentian” baik dalam kitab Perjanjian Lama maupun kitab Perjanjian Baru. Hasil penelitian melalui tiga pendekatan tersebut telah menampilkan adanya peningkatan makna kata “Perhentian” dari konteks Perjanjian Lama dan Perjanjian Baru. Akhirnya, artikel ini dapat mendukung teori pewahyuan progresif yang selama ini diyakini oleh kaum injili dispensasi.